The Role of Duration of Chlorhexidine Gluconate 2% Application on the Shear Bond Strength of a Total Etch Bonding Agent: A Comparative Study - Fasya AN; Yolanda Y; Hayati AT (Dove Medical Press, 2023)
Azmi Nadhira Fasya,1 Yolanda Yolanda,2 Ayu Trisna Hayati2 1Dentistry Undergraduate, Faculty of Dentistry, Universitas Padjadjaran, Bandung, West Java, Indonesia; 2Department of Conservative Dentistry, Faculty of Dentistry, Universitas Padjadjaran, Bandung, West Java, IndonesiaCorrespondence: Yolanda Yolanda, Jalan Dago Pojok No. 23 AB, Bandung, 40135, West Java, Indonesia, Tel +62 856 590 430 30, Email yolanda@unpad.ac.idIntroduction: Matrix metalloproteinases enzymes (MMPs) can degrade the hybrid layer which can cause failure of composite restorations. Chlorhexidine gluconate 2% can reduce MMPs activity and increase the bond strength of the resin to dentin.Purpose: This study aims to determine the role of the duration of chlorhexidine gluconate 2% application on shear bond strength of a total-etch bonding agent.Methods: A total of 36 freshly extracted maxillary premolars were removed occlusally by one-third of the crown using a carborundum disc until the dentin was exposed. Specimens were divided into four groups n(9). The dentin surfaces were etched for 5s. Group A is the control group. In group B, chlorhexidine gluconate 2% was applied for 30s. In group C, chlorhexidine gluconate 2% was applied for 60s. In group D, chlorhexidine gluconate 2% was applied for 90s. The universal adhesive was applied afterwards and then followed by composite to the dentin surface. All specimens were stored in artificial saliva at 37°C for 24 hours. The shear bond strength was tested using a universal testing machine.Results: There was an increase in the shear bond strength of the bonding agent along with the additional application duration of chlorhexidine gluconate 2%. All groups gave higher MPa values than the control group. The shear bond strength in group A (control) was 12.64 MPa; Group B (30s of chlorhexidine) was 16.93 MPa; Group C (60s chlorhexidine) was 18.23 MPa; group D (90s of chlorhexidine) was 18.47MPa.Conclusion: Duration of chlorhexidine gluconate 2% application affects the shear bond strength of the bonding agent with the total-etch system. The effective duration of chlorhexidine gluconate 2% for the restorative procedure is 60 seconds.Keywords: shear bond strength, adhesive system, chlorhexidine gluconate 2%, matrix metalloproteinases, MMPs